Enhancing the contribution of FDI to development : a new agenda for the corporate social responsibility community, international labour and civil society, aid donors and multilateral financial institutions - Moran, Theodore H. (2011)
Advocates that members of international civil society, labour groups, corporate social responsibility advocates, international donors and multilateral lenders should fashion their agenda more closely to provide the external pressures and action need to optimise the impact of mainstream transnational corporate activities on host country growth and welfare.